Mechanical dyssynchrony of the left atrium during sinus rhythm is associated with history of stroke in patients with atrial fibrillation. (27th June 2017) - Ciuffo, Luisa; Inoue, Yuko Y; Tao, Susumu; Gucuk Ipek, Esra; Balouch, Muhammad; Lima, Joao A C; Nazarian, Saman; Spragg, David D; Marine, Joseph E; Berger, Ronald D; Calkins, Hugh; Ashikaga, Hiroshi
Abstract: Aims: We sought to evaluate the relationship between left atrial (LA) mechanical dyssynchrony and history of stroke or transient ischaemic attack (TIA) in patients with atrial fibrillation (AF). We hypothesized that mechanical dyssynchrony of the LA is associated with history of stroke/TIA independent of LA function and C ardiac failure, H ypertension, A ge, D iabetes, S troke/transient ischaemic attack (TIA), VA scular disease, and S ex c ategory (CHA2 DS2 -VASc) score in patients with AF. Methods and results: We conducted a cross-sectional study of 246 patients with a history of AF (59 ± 10 years, 29% female, 26% non-paroxysmal AF) referred for catheter ablation to treat drug-refractory AF who underwent preablation cardiac magnetic resonance (CMR) in sinus rhythm. Using tissue-tracking CMR, we measured the LA longitudinal strain and strain rate in each of 12 equal-length segments in two- and four-chamber views. We defined indices of LA mechanical dyssynchrony, including the standard deviation of the time to the peak longitudinal strain (SD-TPS). Patients with a prior history of stroke or TIA ( n  = 23) had significantly higher SD-TPS than those without ( n  = 223) (39.9 vs. 23.4 ms, P  < 0.001). Multivariable analysis showed that SD-TPS was associated with stroke/TIA after adjusting for the CHA2 DS2 -VASc score, LA minimum index volume, and the peak LA longitudinal strain ( P  < 0.001). The receiver-operating characteristics curve showed that SD-TPS identified patients with stroke/TIA more accurately than CHA2 DS2 -VASc score alone (c-statistics: 0.82 vs. 0.75, P  < 0.001). Conclusion: Higher mechanical dyssynchrony of the LA during sinus rhythm is associated with a history of stroke/TIA in patients with AF.